Currículo e disputas pelo território da geografia na BNCC do ensino médio: implicações para o trabalho docente em Araguaína-TO - MOURA, Osmar Oliveira de (Universidade Federal do Tocantins, 2023)
The National Common Curricular Base (BNCC), approved in 2018, presents changes to the discipline and curriculum of High School Geography, generating professional uncertainties for its teachers. Given this, the present work aims to analyze the transformation of Geography as a curricular component in the area of Human and Social Sciences Applied at BNCC High School and its implications for teachers of state schools in the city of Araguaína-TO. For this, the methodology used in this work was based on a qualitative and exploratory approach, which used bibliographic and documentary surveys, in addition to conducting semi-structured interviews with professionals in Araguaína education (Geography teachers, pedagogical coordinators of Human Sciences and educational advisor) via Google's electronic form. We appropriated the theoretical and methodological references of the Theory of Discourse by Ernesto Laclau and Chantal Mouffe and Stephen Ball's Policy Cycle. Based on the postcritical and post-structuralist perspective of Discourse Theory, we understand the curriculum as a socio-discursive construction, which produces fluid processes of meaning that spreads identities and differences, never finished, always provisional and contingent in places and territories. In this sense, we understand the BNCC as a curricular document, since its text defines questions about what to teach, directly implying the construction of school curriculum. Such document is also interpreted, in this research, as a discourse that seeks a curricular hegemonization, constituted from multiple social actors in different scales of actions, which transformed their private discourses into a universal discourse and which materialized in the approved text the objective of establishing meanings common curriculum in all school spaces. From the analysis of the interviews, we found that Geography at the BNCC of High School is no longer a specific and mandatory subject, but as an integrated knowledge within the area/formative itinerary of Applied Human and Social Sciences, which can bring implications for the pedagogical practice and professional career of teachers of Geography. Therefore, we conjecture that the territory of the discipline of Geography is uncertain and in dispute due to the new changes present in the BNCC of High School, in view of the implications already felt by professionals working in the state schools of AraguaínaTO. However, in our reading, the territory of Geography is threatened by hegemonic discourses present at the BNCC. However, they cannot prevent the creation of other senses and curricular practices in local contexts, aiming at the defense of disciplinary territory